IMPLEMENTASI KEBIJAKAN KONVERSI MINYAK TANAH KE LPG DI KELURAHAN TERBAN KECAMATAN GONDOKUSUMAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA - , Nelly Tiurmida ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study discusses the implementation of policies for kerosene to LPG conversion in the Terban Village, Gondokusuman District, Yogyakarta, Special Region of Yogyakarta, and aims to determine the interpretation of society as a beneficiary, apparatus (RT, RW, headman), and Pertamina marketing manager against the policy, and the implications that arise as a result of differences in the interpretation of the policy implementation kerosene to LPG conversion. This study uses qualitative research methods with a descriptive approach and the method of data collection is done through observation, interviews, and documentation. The data collected and analyzed through three stages, the first data reduction, the second presentation of data, and the third conclusion. Based on the results of the study, it was found that the same interpretation between the public and the authorities on the implementation of policies for kerosene to LPG is given government assistance because kerosene is expensive and hard to come by so hopefully this policy should be continued, accompanied by improved quality of conversion packages that are not easily broken or explode. In contrast, differences in the interpretation of the policy implementation kerosene to LPG, for the community: every citizen entitled to the aid package conversion: for apparatus: changes in the use of fuel switching from kerosene to LPG conversion, and for marketing managers Pertamina as an effort to reduce and save estimate fuel subsidy (fuel oil) to be paid by the state budget (State Budget). Implications arising from different interpretations: people who have used gas (LPG) as a fuel household were given a packet conversion, conversion package apparatus provide to citizens who do not include data collection, and implementation gaps in policy occurred kerosene to LPG conversion. Advice given in this study includes the preparation of activities that need to be carried out by the central government to the distribution point conversion package, so that policy implementation kerosene to LPG conversion can be carried out in accordance with the stated goals and targeted so that the package can be beneficial conversion.